Dampak Perekonomian terhadap Alih Fungsi Lahan Tanaman Kopi ke Tanaman Tomat dalam Peningkatan Kesejahteraan Masyarakat di Desa Potokullin - Sri Selfiani; Nurlianti (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2021)
This study aims to describe the impact of long-term conversion of coffee to tomatoes in the short term. The research was carried out from November to December 2021. Primary data were obtained through interviews with farmers who carried out long-term logging to be converted into short-term planting sites. Secondary data was obtained from the head of the hamlet. Data analysisused is Descriptive Analysis. The results of the study show that from the perspective ofeconomy, land conversion has a positive impact on selling farmer families and the community around. Positive impacts for farming families include increasing family incomefarmers, building farm family houses, opening new farming businesses for familiesfarmers, and for the surrounding community there are job opportunities. From a social point of view, transfer of functionland has positive and negative impacts, namely: changes in the living status of farming families(positive impact), plants are very easily damaged and always take good care (impact negative).